Analisis Implementasi Pemberlakuan UU Nomor 28 Tahun 2009 (Studi Kasus Pengelolaan Penerimaan Pajak Parkir Pada Dinas Pelayanan Pajak Propinsi Daerah Khusus Ibukota Jakarta) - Erniati Rizky Islamiah; Erika Amelia (Esensi: Jurnal Bisnis dan Manajemen, 2015)
This paper contains the analysis of the implementation of enforcement of the law number 28 of 2009, especially in the case management of parking tax revenue in Jakarta. Parking tax revenue in the Province of Jakarta for five years did not reach the target then the author would like to see how the influence of parking tax revenue in the Province of Jakarta after the application of the law number 28 of 2009. The conclusion of this paper is the implementation of Law No.28 of 2009 is essentially no direct effect on tax income in Jakarta provincial park for in the law number 28 of 2009 did not discussin detail about the voting system that is set back in the regulations that made after the application of the law. Influence the application of the law number 28 of 2009 does not provide a positive influence interms of achieving tax revenue target of new parking regulation senacted after that seen in ratio tax revenue target attainment percentage of parking up to the third quarter period after the new regulation simposed.DOI: 10.15408/ess.v5i1.2337